Empowering High School Students through Financial Planning Education at SMAN 5 Parepare, South Sulawesi - Ekasasmita, Wahyuni; Rahmi, Nur; Maratuttahirah, Maratuttahirah; Miftahulkhairah, Miftahulkhairah; Fajri S, Ahmad; Sarmila, Sarmila; Putri, Anggita (Jurnal Pengabdian UNDIKMA, 2024)
This community service aimed to empower high school students by providing education on financial planning at Senior High School 5 Pare pare, South Sulawesi. The methods employed included interactive workshops, presentations, and hands-on activities designed to enhance studentsâ€™ understanding of financial literacy, budgeting, and savings. Pre-test and post-test assessments were administered to measure the participants’ financial literacy levels before and after the intervention. The results demonstrated a significant increase in studentsâ€™ awareness and knowledge of managing personal finances, as reflected in post-workshop surveys and group discussions. Participants showed an improved ability to plan and prioritize their financial goals, contributing to their overall preparedness for future financial challenges. This initiative effectively promoted responsible financial behavior among students.